Sistem Informasi Manajemen Proyek Kontruksi Pada CV. Komitmen Putra Sarolangun - Rizki Anggraini, Ayu; Sharipuddin, Sharipuddin (Jurnal Manajemen Sistem Informasi, 2024)
Analysis and design of a construction project management information system is a system that can minimize errors in the process of making reports on construction projects. The current problem is that the process of recording construction project work still uses telephone media as a means of conveying project progress and then it is recorded back into Microsoft Office Excel where sometimes there are many errors in recording the progress of construction project work, resulting in errors in construction project progress reports. This study aims to analyze the current system requirements and design a construction project management information system with an object-oriented approach using UML (Unified Modeling Language) and prototype models as the methods in this study. This research produces a prototype that can provide solutions and an overview of the design of construction project management information systems such as project worker data designs, client data designs, project activity designs, project budget designs, project documentation designs, and required project reports as well as UML (Unified Modeling) designs. Language) as a tool that can facilitate the developer later in making the system.